PELAKSANAAN PROGRAM PEMASARAN PADA PT. TELKOM (KASUS PELANGGAN PRODUK SPEEDY WILAYAHKOTA PEKANBARU) - Vineza, Yulia; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Problem of this Research is height mount emulation for network of internet at the moment, making PT. Telkom Experience of amount of customer difficult to experience of realyy improvement expected, and surely this time like known by more and more and more amount of consumer of network will make often the happening of network trouble. So that often the happening of trouble make customer dissatisfy and not rarely often do komplein to party to Telkom. As for target of this research that is to analyse execution program marketing At PT. Telkom Pekanbaru Case of customer product of regional speedy Pekanbaru.Execution program marketing At PT. Telkom Case Customer Regional Product Speedy of Pekanbaru Have been execution by according to program which made by a company so that the responder in this case becoming consumer Telkom Speedy can accept their Medial existence Telkom Speedy to be made wrong of product which can be used for network internet at home, form four variable ub covering product quality, price which kompetitif, location and promotion marginally nya asuumed to be executed good enoughly. Is just only still there are insuffiencys in execution program the marketing some becoming feebleness from execution program product marketing this speedy is compared to by other provider of speedy more lambatt send data, amenity system network weared still usemodem fortable so that cannot be borught every where, while provider of other; dissimilar also use modem but can be brought in pocket.Keywords: Marketing , Customer, Service